E-Portfolio as a Support for Teaching Practice at the University of Guayaquil - Vasco Delgado, Juan Carlos; Ortiz Chimbo, Karla Maribel; Ruiz Muñoz, Geovanny Francisco; Romero Amores, Norma Verónica; Macas Padilla, Betty Azucena; Yépez González, David Arturo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This project seeks to highlight the benefits of the implementation and management of the teaching digital portfolio. In today's world full of technology and tools that facilitate daily activities, education and its various processes must also embrace the digital tools available and make them the basis for any innovation and improvement process. The teaching portfolio in physics has long been the means by which teachers have organized the processes, evidence, and other results of educational work. Nowadays, all that range of evidence and productions, which signify the achievement and advances in each group of students, has been able to be integrated into technology.